Newer researchers in higher education: policy actors or policy subjects?. Issue 12 (1st December 2016) - Ashwin, Paul; Deem, Rosemary; McAlpine, Lynn
Abstract : In this article, we explore the extent to which 42 newer researchers, in the academic sub-field of higher education, were aware of, responded to and negotiated their careers in relation to higher education policies. Participants, who were mainly from European countries, tended to divide into two similarly sized groups: one that engaged with and made strategic use of higher education policy, who we termed 'policy actors;' and another who felt that they were shaped by policy rather than working with it, who we termed 'policy subjects.' These differences appeared largely to relate to participants' background prior to studying for their doctorate, their mode of study and doctoral route. All of our participants appeared to perceive the relationship between their research and policies in individual terms, rather than in terms of being a part of a community of higher education researchers. We explore the implications of these findings.